DC–DC converter with high voltage gain and reduced switch stress. Issue 10 (1st October 2014) - Chen, Yie‐Tone; Tsai, Ming‐Hsiu; Liang, Ruey‐Hsun
Abstract : In this study, a novel high step‐up dc–dc converter with high voltage gain and reduced switch stress is proposed. Utilising the coupled inductor to replace the boost inductor for high step‐up converter is widely used in the application of high voltage gain converter. It can not only achieve a high voltage gain but also use the core effectively by using the coupled inductor. The techniques of voltage lift, voltage multiplier and clamp mode are also used in the proposed topology. Furthermore, the proposed converter can avoid the extreme duty cycle that will cause a lot of conduction losses. The leakage inductance energy of the coupled inductor will cause a huge voltage on the components of circuit, so that it needs to choose the components with high voltage and current ratings; then the efficiency is reduced and the cost is increased. The converter proposed in this paper can not only recycle the leakage inductance energy to the output but also increase the efficiency. A 300 W prototype converter which is implemented with an input voltage of 26 V and an output voltage of 400 V will demonstrate the effectiveness of this proposed converter.